3 ft = 1 yd 6 ft = 2 yd 9 ft = 3 yd . . 36 ft = 12 yd
1 yd = 3 ft 4 yd = 12 ft 4 yd and 2 ft = 14 ft
Given: 1 yard = 3 feet Squaring both sides of the equation: (1 yd.)2 = (3 ft.)2 1 yd.2 = 9 ft.2 Convert: 60 yd.2 X (32 ft.2/12 yd.2) 60 yd.2 X (9 ft.2/1 yd.2) = 540 ft.2 60 square yards = 540 square feet
2 yd 2 ft
9 yd 2 ft. Incidentally, 2 yd 4 ft is a strange way of representing a distance of 3 yd 1 ft.
36 yd and 2 ft = 110 ft, which is certainly not equal to 114 1/6 ft.
3 ft = 1 yd 6 ft = 2 yd 9 ft = 3 yd . . 36 ft = 12 yd
1 yd = 3 ft 4 yd = 12 ft 4 yd and 2 ft = 14 ft
Given: 1 yard = 3 feet Squaring both sides of the equation: (1 yd.)2 = (3 ft.)2 1 yd.2 = 9 ft.2 Convert: 60 yd.2 X (32 ft.2/12 yd.2) 60 yd.2 X (9 ft.2/1 yd.2) = 540 ft.2 60 square yards = 540 square feet
2 yd 2 ft
9 yd 2 ft. Incidentally, 2 yd 4 ft is a strange way of representing a distance of 3 yd 1 ft.
8 yards 2 feet - 5 yards 1 foot = 3 yards 1 foot
1 yd = 3 ft 1 ft = 12 inches therefore, 1 yd = 36 inches answer: 2 yards
14 feet or 4 yd 2 ft
52 yd 1 ft - 17 yd 2 ft = 51 yd 4 ft - 17 yd 2 ft = 34 yd 2 ft
1 yd. 2 ft.
The Answer is 2 yd 9 ft because its like 51-22=29